2010
DOI: 10.4103/0378-6323.66581
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus in children

Abstract: Lichen planus in children is considered to be rare overall, though it does not appear to be so in Indian subcontinent. Most of the large studies on lichen planus in children have been undertaken in India. We review here the epidemiology, pathogenesis, clinical features, diagnosis, management and prognosis pertaining to lichen planus in children with emphasis on studies published from India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 24 publications
4
36
1
4
Order By: Relevance
“…2 Though the world wide prevalence of childhood lichen planus is rare, for reasons unknown, it is not that uncommon in India, based on the fact that the largest case series on childhood LP are published NJDVL -2 from India. [3][4][5][6] In a study from UK also it was found that children originating from the Indian subcontinent represented 80.8% of children with lichen planus suggesting that children from South Asian origin are more susceptible to developing LP. 7 This could be attributed to the difference in the genetic background and environmental triggers or underreporting in other areas.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…2 Though the world wide prevalence of childhood lichen planus is rare, for reasons unknown, it is not that uncommon in India, based on the fact that the largest case series on childhood LP are published NJDVL -2 from India. [3][4][5][6] In a study from UK also it was found that children originating from the Indian subcontinent represented 80.8% of children with lichen planus suggesting that children from South Asian origin are more susceptible to developing LP. 7 This could be attributed to the difference in the genetic background and environmental triggers or underreporting in other areas.…”
Section: Epidemiologymentioning
confidence: 99%
“…[3][4][5][6]8 Majority of the studies, either the sexes were equally affected or there was marginal male preponderance. 4 Familial LP occurs in 1-2% of all childhood cases and these differ from the classical form clinically, with earlier age at onset, more generalized involvement, more common mucosal involvement and an increased tendency for erosive, ulcerative and linear forms, with prolonged course and frequent relapses. 4 Etiology LP is a T-cell-mediated autoimmune damage to basal keratinocytes, which have been altered by viruses, medications, or other unknown allergens.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations